Consensus in franchise organizations: A cooperative arrangement among entrepreneurs - Baucus, David A.; Baucus, Melissa S.; Human, Sherrie E. (Journal of Business Venturing, 1996)
Entrepreneurs enter into cooperative arrangements such as franchise systems (Baucus, Baucus and Human 1993; Norton 1988), network partnerships (Larson 1991, 1992), and constellations of firms (Shepherd 1991) to gain a competitive advantage over rivals (Baird, Lyles and Orris 1992; Larson 1992). They expect to reduce production and inventory costs, speed product development, expand markets, or secure technology, while enjoying congenial business relations with partners (Larson 1992). Entrepreneurs may not reap advantages attributed to cooperative arrangements, however, if dissension arises concerning the means of competition or desired ends. Strategic management researchers associate competitive advantage in part with consensus on the means of competition (e.g., Bourgeois 1980; Dess and Davis 1984), whereas entrepreneurship researchers accentuate the importance of common ends (e.g., goals and values) in cooperative arrangements (Ambrose and Koepke 1984; Larson 1991; Mohr and Spekman 1994; Shepherd 1991; Starr and MacMillan 1990). Competitive advantage refers to the superior capabilities of the firm over rivals (Porter 1980) and means of competition involve resource allocations (Dess and Davis 1984; Porter 1980). Desired ends include business goals, as well as standards of fairness and trustworthiness (Larson 1991). Strategy researchers report that consensus among managers on methods of competing relates to higher firm performance (Bourgeois 1980; Dess and Davis 1984), but they have not shown that within-firm results generalize to cooperative relations. We believe consensus on means and ends may command a particularly important influence on the competitive advantage of franchises, network partnerships, and constellations of loosely tied entrepreneurs. Franchising pioneers like Bill Rosenberg (Dunkin Donuts) and Frank Carney (Pizza Hut) created a context of trust and respect with franchisees (Tannenbaum 1993a), but the physical separation, disparate challenges, and incongruous goals of franchisors and franchisees (Norton 1988; Phan, Butler, and Lee 1996) now produce widespread dissension. Franchise partners join separate professional associations, such as the International Franchise Association and American Franchisee Association, potentially dividing loyalties. Franchisees initiate class-action lawsuits and conduct grassroots lobbying, whereas franchisors arbitrate disputes through professional associations and advisory boards (Galen and Touby 1993; Tannenbaum 1993a). The litigious nature of the U.S. society may accentuate dissension among franchise partners, but franchise systems worldwide may soon exhibit similar tendencies. Similarly, network partnerships, defined as close collaborative alliances between entrepreneurs and a limited set of resource partners (Larson and Starr 1993), begin as arms-length, adversarial transactions and evolve into relationships based on trust. They require reciprocity, collaboration, complementary interdependence, and mutual understanding of partners' business styles and motives (Larson 1992). Constellations refer to clusters of complementary firms organized into coordinated partnerships with lead firms; they require firms to develop precise roles and known rules of operation (Lorenzoni and Ornati 1988). Entrepreneurs reaching consensus with their franchise, network, or constellation partners on means and ends may secure the advantages of cooperation and outperform rivals; those lacking consensus likely face recurring conflicts, disappointing performance, and the eventual dissolution of partnerships. Entrepreneurship researchers have not yet examined consensus on means and ends of cooperative arrangements among franchisees, or other entrepreneurs, and they have not tested linkages between consensus and competitive advantage. Prior authors have described competitive advantages of selecting a franchise over an independent business (Ayling 1988; Baron and Schmidt 1991; Knight 1986) and conditions giving rise to franchise arrangements (Norton 1988). They have studied the formation of partnerships (Larson, 1991, 1992), described the normative operations of constellations (Shepherd 1991), and enumerated impressive benefits of such arrangements (Baird et al. 1992; Larson 1991). Yet, normative guidelines for forming partnerships overlook the hazards stemming from dissension in such relationships (Mohr and Spekman 1994). We examine perceived consensus on indicators of the means of competition (e.g., priorities in resource allocations), and analyze how consensus on means and ends (e.g., goals and values) relates to competitive advantage and performance in franchise systems, the most pervasive and fastest growing form of cooperative venture among entrepreneurs. Franchises represent an ideal context for our study, because widespread disputes occur among franchisees and franchisors, especially as franchisors modify strategies to offset the effects of rising competition (Barrett 1992). The lack of consensus in franchise relationships has triggered extensive investigations by states, Congress, and the FTC to protect franchisees from misrepresented products or cannibalized retail outlets (Marsh 1992). We report statistically significant differences between franchisees' emphasis on competitive methods and those they attribute to their franchisor. These differences occur in franchisee-franchisor relations despite evidence that consensus relates positively with the franchise's competitive advantage, business performance in retail operations, and franchisees' satisfaction. We believe dissension arises as franchisees initially move from a knowledge disadvantage relative to franchisors to a knowledge advantage associated with the accumulation of local experience. Early in the relationship, franchisees need advice and franchisors police franchisees to comply with standards for operations, as accepted theories imply (e.g., Brickley, Dark and Weisbach 1991). Over time, franchisees gain local knowledge about their markets, exercise entrepreneurial initiative, and adopt their own standards for quality and conduct. Dynamic attributes of franchise relationships requires further investigation, but theories promoting monitoring and policing actions by franchisors may better describe relationships with new or renegade franchisees, rather than with franchisees like those in our sample. Our study contributes to the entrepreneurship literature by integrating cooperative arrangements research with consensus studies in strategic management. We frame franchise relationships as one form of cooperative arrangement among entrepreneurs, and believe our study of franchises should shed light on relationships between consensus and performance in other cooperative arrangements. We operationalize competitive advantage using dimensions critical for competing in the fast food industry, the context of our investigation, demonstrating how entrepreneurship researchers may move beyond loose (unmeasured) treatments of the concept. We begin with explanations of franchise arrangements and dissension in cooperative arrangements, then present our hypotheses. A description of our methods and results follows, along with a discussion of the implications of our study for franchisors, franchisees, and researchers.